2017
DOI: 10.1186/s40580-017-0123-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured porous graphene and its composites for energy storage applications

Abstract: Graphene, 2D atomic-layer of sp2 carbon, has attracted a great deal of interest for use in solar cells, LEDs, electronic skin, touchscreens, energy storage devices, and microelectronics. This is due to excellent properties of graphene, such as a high theoretical surface area, electrical conductivity, and mechanical strength. The fundamental structure of graphene is also manipulatable, allowing for the formation of an even more extraordinary material, porous graphene. Porous graphene structures can be categoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 153 publications
(322 reference statements)
0
19
0
Order By: Relevance
“…Graphene is a single layer honeycomb structure of carbon lattice [ 1 ] with many interesting behavior and characteristics [ 2 ]. It is considered the most promising material for engineering design due to its extraordinary electrical, mechanical, and chemical properties [ 3 , 4 , 5 ]. Since 2004, the exfoliation of single-layer graphene [ 6 ] has been investigated and explored in every field of science.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a single layer honeycomb structure of carbon lattice [ 1 ] with many interesting behavior and characteristics [ 2 ]. It is considered the most promising material for engineering design due to its extraordinary electrical, mechanical, and chemical properties [ 3 , 4 , 5 ]. Since 2004, the exfoliation of single-layer graphene [ 6 ] has been investigated and explored in every field of science.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, materials are deposited selectively on chemically active regions such as line defects . In recent years, graphene composites have been actively investigated for many applications. , Graphene–metal composites with metals such as Ru and Pt, acquired by selective deposition, have demonstrated that the electrical properties of graphene are improved. Hydrogen detector applications are also feasible.…”
Section: Introductionmentioning
confidence: 99%
“…The pores in graphene can be classified as microporous (<2 nm), mesoporous (2–50 nm), and macroporous (>50 nm) according to the definition by International Union of Pure and Applied Chemistry (IUPAC). 46,47 In the following section, these synthesis methods are discussed in detail.…”
Section: Synthesis Of Holey Graphenementioning
confidence: 99%